Identification of RNPC3 as a novel JAK2 fusion partner gene in B‐acute lymphoblastic leukemia refractory to combination therapy including ruxolitinib. Issue 3 (30th December 2019) - Chen, Xue; Wang, Fang; Zhang, Yang; Ma, Xiaoli; Liu, Mingyue; Cao, Panxiang; Zhou, Lin; Wang, Lan; Zhang, Xian; Wang, Tong; Liu, Hongxing
Abstract: Background: Hematopoietic neoplasms with chromosomal translocations involving JAK2 are rare, and most of them show myeloproliferative neoplasm‐associated features, followed by B‐acute lymphoblastic leukemia (B‐ALL). De novo B‐ALL cases with JAK2 rearrangements are suggested to be appropriately considered as BCR‐ABL1 ‐like B‐ALL, but its partners varied. Methods: Fluorescence in situ hybridization (FISH), RNA sequencing (RNA‐Seq), whole‐genome sequencing, and reverse transcription polymerase chain reaction (RT‐PCR) were performed to identify the pathogenic fusion gene in a 29‐year‐old woman with relapsed B‐ALL and rare t(1;9)(p13;p22) translocation. Results: We identified RNPC3 as a new JAK2 fusion partner in the patient. She was treated with a combination of chemotherapy and targeted drug ruxolitinib and chimeric antigen receptor T‐cell therapy, but failed to achieve complete remission. She had no chance to undergo allogeneic hematopoietic stem cell transplantation and died of disease progression 7 months after the initial diagnosis. Her clinical course demonstrated that this novel RNPC3‐JAK2 fusion might portend an unfavorable prognosis. Conclusion: This finding adds to the expanding compendium of JAK2 fusions found in B‐ALL and suggests the potential need for a diagnostic FISH analysis as well as RNA‐Seq in the appropriate clinical setting. Abstract : We identify RNPC3 as a new JAK2 fusion partner in a 29‐year‐old female with relapsed B‐ALL by fluorescence in situ hybridization (FISH), RNA sequencing (RNA‐Seq), whole‐genome sequencing, and RT‐PCR. Her clinical course demonstrated that this JAK2 rearrangement might portend an unfavorable prognosis. This finding adds to the expanding compendium of JAK2 rearrangements found in B‐ALL and suggests the potential need for a diagnostic FISH analysis as well as RNA‐Seq in the appropriate clinical setting.